A Review on "Ocuserts (An Ophthalmic Insert)” - Nidhi A. Bagmar; Pooja R. Hatwar; Prashant G. Shelke; Dr. Ravindra L. Bakal (Asian Journal of Pharmaceutical Research and Development, 2024)
The eye is God's most wonderful creation of all the sense organs in the human body since it allows us to see numerous objects both near and far away. An ocular implant is a cutting-edge device for treating eye diseases. The design and development of an ocular insert has always been a difficulty for pharmaceutical researchers and manufacturers. Ocuserts, also known as ophthalmic inserts, are "sterile preparations in the form of solid or semisolid, whose size and shape are specially designed to be applied to the eyes". Solvent casting, the Glass Substrate technique, and hot melt extrusion were used to create ocuserts. The inserts can be classed as insoluble, soluble, or biodegradable based on their solubility. The drug's release from the insert is determined by its diffusion, osmosis, and bioerosion. The ocuserts' objective is to enhance pharmaceutical contact with conjunctiva tissue, resulting in constant dose release. Uniform ocular drug levels reduce systemic side effects, minimise doses, and improve patient compliance. Preparing ocular inserts aims to enhance medication bioavailability. Ocular inserts keep medication concentrations within the appropriate range. Using fewer administrations leads to better patient compliance. The page covers the eye's many parts and anatomy, along with an explanatory image.This study aims to offer an update on current understanding in ocular medication delivery. Also, this review focuses on the current usage of ocuserts to treat eye disorders.